(untitled) (Global Journal of Management and Business Research, 2019)
Liquidity crisis is severe in Bangladesh commercial Banks and eventually some commercial banks suffered due to higher default and liquidity problem. This paper aims to empirically study the relationship between liquidity and financial performance of Commercial banks in developing country like Bangladesh. The investigation has been performed using panel data procedure for a sample of Dhaka stock market enlisted all commercial banks (31) during the year of 2010-2017. Our result shows that liquidity has no significant and positive or negative impact on return on asset (ROA), return on equity (ROE) as financial performance. Liquidity risk behaves in equivalent ways in different dependent variables.